(3GdbVGA hGdbOQ aj GdbQBf hGdSfI hGdacQ GdESdGej (B/s - (3SdWGf, YHO GdeMSf YHO GdebUhO eMeOs ((3GdbGgQI (B:s (3ecJHI hgHI,s, 2000)
(3BQGA GdaQb GdESdGejI(B.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B.s
Keywords: (3GdbQBfs -- (3Ydhes; (3GdbVGA hGdbOQs; (3GdEjeGfs